Genotyping test based on viral DNA, RNA or both as a management option for high-risk human papillomavirus positive women: a cross sectional study - Irma Salimović-Bešić; Anja Tomić-Čiča; Mirsada Hukić (Medicinski glasnik, 2019)
Aim: This cross-sectional study of a group of women with abnormal cytology and high-risk human papillomavirus (hrHPV) infection compared genotyping HPV DNA and mRNA assays according to two age categories of women (S1: ?30 and S2: >30 years). Methods: The hrHPV DNA positive results of 105 cervical samples of women were pooled and those harbouring HPV-16, 18, 31, 33 and/or 45 DNA were tested for the type specific HPV oncogene E6/E7 overexpression (mRNA). Results: Although HPV DNA testing showed a higher proportion of women infected by any of five hrHPVs in S1 group, total agreement of hrHPV DNA and mRNA positive results was higher in S2 group of women (75.8% v. 83.9%). The most prevalent type in both age groups was HPV-16. A 100% agreement of positivity of both tests was noted for HPV-18 and 33 in S1 group, and for HPV-18 in S2 group. Increasing concordance of HPV-16 and 31 DNA and mRNA positive results with the severity of cervical cytology was observed in S1 group of women. Absolute matching (100.0%) of positivity of both diagnostic tests was recorded in S2 ASCUS group (for HPV-16, 18 and 33), in S1 HSIL (for HPV-16, 18, 31 and 33), in S1 LSIL category (for HPV-18 and 33) and in S2 HSIL group (for HPV-18). Conclusion: The results indicate the possibility of predicting the risk of persistent infection only by HPV DNA typing test, with no need for additional RNA testing in categories of infected women showing a high (absolute) agreement of positivity of both tests.
Keywords: biomarkers; early detection of cancer; human papillomavirus DNA tests; human papillomavirus 16; human papillomavirus 18